Reliability and validity of a new specific field test of aerobic capacity with the ball for futsal players - Barbieri, R.; Barbieri, F.; Milioni, F.; dos Santos, J.; Soares, M.; Zagatto, A.; Papoti, M. (International Journal of Sports Medicine, 2017)
The aim of this study was to establish the validity and reliability and verification of the reproducibility of the lactate minimum test (LM) to predict the maximal lactate steady state exercise intensity (MLSS) on a futsal-specific circuit (Futsal_circuit) which takes into consideration the technical movements performed. 16 male Brazilian futsal players (body mass: 67.7±8.3 kg; height: 1.73±0.05 m) were distributed randomly into 2 studies with 8 athletes in each (Study A - reproducibility; Study B - validity). First, aerobic capacity was determined by adapting the protocol of the LM to the futsal_circuit. In study A, the evaluation was repeated after 7 days (test e re-test) and, in study B, the MLSS on the futsal_circuit was performed. LM intensity (test=7.7±0.3 km.h-1; retest=7.7±0.4 km.h-1) showed a concordance (CV=4.13 and ET=0.32) on study A. No significant differences, high association (r=0.80; p<0.05) and concordance (lower limits: -0.58 km.h-1; Upper limits: 0.55 km.h-1) between LM and MLSS (7.5±0.5 km.h-1 LM; 7.5±0.4 km.h-1 MLSS) on study B. According to the results, we can conclude that the Futsal_circuit is reliable, reproducible and valid for assessing the functional aerobic capacity of futsal players.